KOLABORASI PESANTREN DAN TENAGA KESEHATAN DALAM MENINGKATKAN PEMAHAMAN PHBS DAN KESEHATAN REPRODUKSI WANITA DI PESANTREN RUMAH QUR’AN UMAR BIN KHATTAB KABUPATEN BOGOR - Sri Rahayu; Mulyanti Mulyanti; Rina Yuliana Subur (LPPM Institut Pendidikan Nusantara Global, 2025)
Pesantren as a religious-based educational institution has an important role in shaping the pattern of Clean and Healthy Living Behavior for santri and santriwati. However, there are still challenges in improving knowledge, understanding and application of Clean and Healthy Living Behavior (PHBS) and Female Reproductive Health among female santri. This community service program aims to improve knowledge, understanding and application of PHBS regarding Female Reproductive Health at the Umar bin Khattab Qur'an House Islamic Boarding School, Bogor Regency. The methods used include counseling education, and direct observation practices to 110 female students through a participatory and interactive approach. The evaluation results showed that there were scores > 60 in PHBS knowledge of 104 santriwati (94.55%), awareness of female reproductive health with scores > 60 only 30 santriwati (27.27%). In addition, the implementation of PHBS in the pesantren environment based on observation and assessment, there are still scores with low scores <60 on the following indicators; cleanliness of ablution places; use of healthy bathrooms & latrines; dormitory cleanliness and sufficient ventilation; water reservoirs & used goods free of mosquito larvae; santri utilize poskestren & health service facilities; know priority health information; and have health care insurance. In conclusion, this educational intervention proved to be effective in improving the knowledge and behavior of santriwati towards PHBS and Reproductive Health. It is expected that similar programs can be implemented in a sustainable manner with the collaboration of Cross Sector and Cross Program pesantren with the local Health Office to create a healthier pesantren environment.